Perbandingan Persepsi Kepuasan Mahasiswa Antara Pembelajaran Menggunakan Blended Learning Dan Online Learning - Alfrits Roul Sinadia; Petrus Kondo (Journal on Education, 2023)
This study was conducted to examine the perception of student satisfaction with the use of two learning models, namely blended learning before the COVID-19 pandemic and online learning during the COVID-19 pandemic. Specifically, it aimed to draw conclusions on differences in student satisfaction levels when using blended learning and online learning, which includes the learning process, learning assessment, learning load, lecturer and student discipline, and social interaction among lecturers and students, or social interaction among students and students. It was quantitative research using descriptive and inferential statistical analysis. The data collection was conducted through an online questionnaire filled out by 140 respondents. The results showed that students felt more satisfied with the blended learning model than the online learning model. Students showed more satisfaction in the learning process, student discipline, social interaction among lecturers and students, or social interaction among students and students